2017
DOI: 10.1080/15374416.2017.1342546
|View full text |Cite
|
Sign up to set email alerts
|

Parental Self-Efficacy to Support Teens During a Suicidal Crisis and Future Adolescent Emergency Department Visits and Suicide Attempts

Abstract: This study of adolescents seeking emergency department (ED) services and their parents examined parents' self-efficacy beliefs to engage in suicide prevention activities, whether these beliefs varied based on teens' characteristics, and the extent to which they were associated with adolescents' suicide-related outcomes. Participants included 162 adolescents (57% female, 81.5% Caucasian), ages 13-17, and their parents. At index visit, parents rated their self-efficacy to engage in suicide prevention activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
0
26
0
1
Order By: Relevance
“…Proximal risk factors are factors that predict the short-term occurrence of suicidal behaviors (11). Recently, there has been an increase in research that investigated proximal risk factors of suicidal ideation in daily life, of which most are based on Joiner's interpersonal theory of suicide (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Proximal risk factors are factors that predict the short-term occurrence of suicidal behaviors (11). Recently, there has been an increase in research that investigated proximal risk factors of suicidal ideation in daily life, of which most are based on Joiner's interpersonal theory of suicide (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In CLASP-A, we made it mandatory that parents/guardians were in the support role as they are typically the adults with whom adolescents are most engaged. However, parents of adolescents who attempt suicide may have lower self-efficacy in supporting their child through a suicidal crisis (Czyz, Horwitz, Yeguez, Ewell Foster, & King, 2018). Furthermore, family factors, such as family dysfunction or complexity, maternal psychopathology, and quality of the parent–child relationship, compromise treatment follow through (King, Hovey, Brand, Wilson, & Ghaziuddin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…One parent stated that learning the signs of an impending suicide attempt was important to them as this could potentially include the child's behaviors and communication with family and friends before the suicide attempt. This is a recurrent theme in the literature as Czyz et al (2018) found parents had doubts in their ability to keep their child safe if the teen has suicidal ideation in the future. McDonald et al (2007) also found that mothers felt guilty that they were unable to recognize their children were so deeply unhappy.…”
Section: Discussionmentioning
confidence: 99%
“…Although not specifically asking parents which supports they needed, Czyz, Horwitz, Yeguez, Ewell Foster and King () examined the self‐efficacy of parents to engage in prevention and management of their child's suicidal crisis when seeking psychiatric emergency services. The authors found most parents of high‐risk teens did feel confident in their ability to maintain safety for their child; however, the parents did not feel comfortable in their ability to recognize warning signs of another suicide attempt.…”
Section: Introductionmentioning
confidence: 99%